Examination of the Sufficiency of Small Qualitative Samples. - Young, Diane S; Casey, Erin A (Social Work Research, 2019)
The article discusses the ideal minimum sample sizes that are needed to achieve meaningful results in qualitative studies. Also cited are the studies which analyzed sample size through the use of various definitions of data saturation or code saturation, as well as the various studies used to gather data including the Men Against Violence (MAV) study, the Social Workers in Criminal Justice (SWJC) study, and the Adolescent Bystander Behavior (ABB) study.